Effect of Al2O3 on structural and dielectric properties of PVP-CH3COONa based solid polymer electrolyte films for energy storage devices. Issue 10 (October 2019) - Kumar, M. Seshu; Rao, M.C.
Abstract: Nanocomposite polymer (NCP) films were prepared by doping sodium acetate (CH3 COONa) in polymer of polyvinyl pyrrolidone (PVP) by complete dispersion of aluminum oxide (Al2 O3 ) with different wt% proportions using solution cast method. The acquired NCP films were systematically characterized. The crystalline structure of the prepared NCP films was confirmed by XRD. The little agglomeration and grain sizes involved in the films were analyzed by SEM. The chemical bond formation and interchange reaction between the host, dopant salt and the nanofiller were confirmed by FTIR and Raman. The lowest energy bandgap values were observed to be 3.0 eV for the synthesized film with wt% ratio of PVP + CH3 COONa:Al2 O3 (80:20:1%). The highest ionic conductivity was found to be 1.05 × 10 −3 S/cm for the prepared film with wt% ratio of PVP + CH3 COONa:Al2 O3 (80:20:1%). From the charge discharge characteristics it was concluded that the film with wt% ratio of PVP + CH3 COONa:Al2 O3 (80:20:1%) possesses long durability when compared to the other prepared films. Abstract : Electrochemistry; Materials chemistry; Materials science; Nanocomposite polymer films; Solution cast technique; XRD; FTIR; Raman; AC conductivity; Cyclic voltammetry